Multimedia Elements in the Motion Tracking Effect of Taekwondo Martial Arts Learning Media - Aulia Hamdi; Andriyan Widiyanto; Luky Rafi Anuggilarso; Anugerah Bagus Wijaya (Jurnal Teknologi Informasi dan Pendidikan, 2022)
Taekwondo is a modern martial art originating from traditional Korean martial arts. That is the art or type of self-discipline or Pencak silat that uses bare hands and feet. The basics of taekwondo consist of offensive and defensive movement techniques that use the body to confront the enemy. Taekwondo focuses more on kicks than punches. Kicking techniques are generally more complex than the hands, but kicking techniques are the main because their strength is greater than the strength of the hand. With proper and correct training methods, the quality of kicks can be significantly improved. In taekwondo, it is not just a means of self-defense. With the development of today's technology, it may be more effective to provide taekwondo training materials. Video media has the advantage of being easy to learn. Watching videos to learn movement techniques does not have to be during practice. It can be done anywhere. In addition, you can play the video repeatedly and slow down to see the train technology. From the opinion of experts, it can be concluded that the media is a sub tool used to convey information to students as recipients of information designed to increase student interest in learning. In the research and development carried out, Taekwondo training is packaged in VCD format as a medium to be displayed via an LCD projector during learning.